More than meets the eye: a case of HCV-induced PAN. Issue 2 (3rd July 2018) - Kumthekar, Anand; Wolf, Bryan; Woltjer, Randy; Schwab, Pascale
Abstract: A 60-year-old male with a history of chronic active hepatitis C (HCV) was admitted for evaluation of subacute, additive weakness and pain of his upper and lower extremities along with jaw claudication and constitutional symptoms. Examination confirmed the presence of asymmetrical distal and proximal weakness along with sensory deficits and painful dysesthesias. Laboratory testing revealed anaemia of chronic disease, leucocytosis, thrombocytosis, as well as elevated creatinine kinase, sedimentation rate and C-reactive protein. HCV antibody and viral RNA were positive. An MRI of the thighs showed multifocal T2 hyperintensity on fat suppressed sequences, and electromyogram and nerve conduction study demonstrated a proximal myopathy with multiple bilateral mononeuropathies. A sural nerve biopsy was inadequate, but a left vastus lateralis muscle biopsy revealed widespread myopathic changes and a medium vessel with sequelae of vasculitis. In light of the additive mononeuritis multiplex and the medium vessel vasculitis on muscle histopathology, a diagnosis of hepatitis C-related polyarteritis nodosa (PAN) with resultant muscle necrosis was made. He was treated with immunosuppression and direct-acting antivirals with excellent clinical outcome.